ANALISIS EFISIENSI MODAL KERJA DAN RENTABILITAS MODAL SENDIRI PADA KOPERASI KARYAWAN KEBUN/PKS/PLASMA SEI PAGAR (KOPKAR SPA) - Reni Yulianthi; Gusnardi '; Gani Haryana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Coorperation will basically targeted activities to achieve goals. Where each activity is run coorperations in need of funds used to carry out activities of the coorperation is called working capital. Analysis of working capital related to the source and its use will help the parties concerned to find out how to manage working capital efficiently and effectively to improve the return of the coorperation. The purpose of this study is to investigate the efficiently of working capital and return on equity. The method used is descriptive, with a comparative analysis of the financial statements and conclusion. Results obtained by the analysis of financial statements that koperasi karyawan kebun/PKS/plasma Sei Pagar (KOPKAR SPA) working capital and return on equity changes every year. Management coorperations should do the planning in managing working capital and other coorperation funds, this is because the position of assets for the years 2010 to 2014 is not stable, if this is the case it is feared return on equity declined.Keywords: Efficiency of Working Capital and Return on Equity